On the origins of x in Slavic - Ondřej Šefčík (Linguistica Brunensia, 2013)
This paper focuses on three regular sources of x in the Slavic languages. Beside the well-known source Pedersen's Law, there are two minor regular sources, namely the clusters *sk and *kH2. Especially the last source is the only remaining proof of secondary "voiceless aspirates" in Balto-Slavic, since all other clusters of voiceless stop + laryngeal disappeared without a trace in Balto-Slavic. Slavic x is thus heir to three regular independent processes, which merged into a single result. This resulting x was later supported by loanwords and onomatopoeic words, but none of those secondary sources is relevant, as they are not part of the system for x given by those three above-mentioned regular processes.